Missed opportunities for screening congenital syphilis early during pregnancy: A case report and brief literature review - Peng, Lei-Wen; Gao, Yu-Jie; Cui, Ya-li; Xu, Huang; Gao, Zheng-Xiang (Frontiers in Public Health, 2023)
Congenital syphilis is a significant public health problem. Pregnant women infected with Treponema pallidum present with various clinical manifestations, mainly including skin or visceral manifestations. The extensive clinical manifestations of T. pallidum infection mimic those of many other diseases during pregnancy, which may lead to delayed diagnosis and serious consequences. We report a case of fetal T. pallidum infection and premature delivery in a woman whose syphilis screening was negative at 16 weeks of gestation. Despite presenting to the dermatologist at 24 weeks of gestation with maculopapular rash which is usually associated with secondary syphilis, the diagnosis of syphilis was not considered. This case shows that even if early syphilis screening of pregnant women is negative, they may still get infected with T. pallidum later on in pregnancy. Therefore, in patients presenting with a rash without an obvious cause, T. pallidum infection should be excluded. The health status of patients' spouses should be assessed during pregnancy. Additionally, perinatal health education is necessary for women and their spouses during pregnancy. The abovementioned factors could reduce the probability of T. pallidum infection in pregnant women and their infants.